Gambaran Penggunaan Air Bersih Di Kelurahan Malalayang 1 Kota Manado - Lampus, Benedictus S.; Lumintang, Marlon B.M.; Siagian, Iyone E.T. (UNIVERSITAS SAM RATULANGI, 2013)
Water is a basic human need which is used as an instrument of human survival. Water used for drinking, preparing food, cleaning the body and household items, as well as the management of the environment. The use of water have an effect on public health because water source contaminated lot. This research was conducted to find out the descrip-tion of the usage of clean water in Malalayang 1 sub-district society. As for the research use descriptive method using the methods of the survey. The sample used was 100 respondents using proportional random sampling method from 2412 head family in Malalayang 1 sub – disctrict society. Data is processed based on the presentation of the respond-ent's answer. Results of the study found that users of PT.Air 64% have the physical state of water does not taste and smell and 72% have clear water. For users of the well pump is 17.3% have < 10 meters of distance of the well pump and pit latrines / garbage. So in the use of public water PT.Air 52% use water to wash clothes and equipment and the community who use the well pump 61,3% use water for hygiene (shower, brush your teeth).Keywords: the use of water, PT.Air, pump well